Flavonoids of Lysimachia atropurpurea L. - (:unkn) unknown (My University, 2003)
The ethanolic extract of the aerial parts of Lysimachia atropurpurea were investigated. The isolated. compounds were kaempferol(1), quercelin(2), apigenin-7-O-glucoside(3), luteolin(4), kampferol 3-O-galactoside(5).
Keywords: Flavonoids; Lysimachia atropurpurea